DOI: 10.33915/etd.5823
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Electronic Cigarette Use on Glucose Metabolism

Abstract: Effects of Chronic Electronic Cigarette Use on Glucose Metabolism Hannah Hoskinson Traditional cigarette usage has been linked to a number of nefarious metabolic effects, including insulin resistance; however, the effects of electronic cigarettes (E-cigs) are not currently known. Advertised as a safe alternative for traditional tobacco cigarettes, E-cigs still contain some of the same harmful chemicals as tobacco cigarettes. Through this study, we hope to gain perspective on whether e-cigs play into the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…One of the previous studies revealed that cigarette smoking was associated with an increase in HbA1c in the general population [ 19 , 20 ]. In addition, one study found that e-cigarettes smokers are likely to have a high HbA1c level compared to cigarette smokers [ 21 ]. A possible explanation for this could be the increase in the rate of glycation of HbA1c induced by exposure to glycotoxin from cigarette smoke or the relatively high degree of tissue hypoxia [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the previous studies revealed that cigarette smoking was associated with an increase in HbA1c in the general population [ 19 , 20 ]. In addition, one study found that e-cigarettes smokers are likely to have a high HbA1c level compared to cigarette smokers [ 21 ]. A possible explanation for this could be the increase in the rate of glycation of HbA1c induced by exposure to glycotoxin from cigarette smoke or the relatively high degree of tissue hypoxia [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several longitudinal studies have demonstrated that smoking is associated with diabetes 19,20 . However, few studies have con rmed a link between e-cigarette use and prediabetes 21 . Considering that adults often use a mixture of e-and c-cigarettes to reduce or quit c-cigarettes rather than smoking e-cigarettes alone, our research shows the association of e-cigarettes with prediabetes.…”
Section: Discussionmentioning
confidence: 99%